SANKSI PIDANA DAN GANTI RUGI PERDA DALAM KASUS PENYEBARAN PENYAKIT MENULAR AKIBAT PELANGGARAN PROTOKOL KESEHATAN: STUDI KATASTROPI PANDEMI DAN REGULASI PASCA-COVID-19 - Gunawan Widjaja (Jurnal Kesehatan, 2026)
This article examines criminal penalties and compensation under Local Regulations (Perda) for cases of the spread of infectious diseases resulting from violations of health protocols, using the COVID-19 pandemic as a case study and post-COVID-19 regulations as a framework for normative evaluation. This study aims to analyze the basis for establishing criminal sanctions in Perda, examine the possibility of awarding damages to victims of transmission, and assess the direction of local regulatory reform following the pandemic. The method used is a literature review employing a descriptive qualitative approach through an examination of legislation, legal literature, and scientific sources relevant to health law, criminal law, and civil liability. The results of the study indicate that criminal sanctions in local regulations serve as a coercive instrument to ensure compliance with health protocols, particularly when violations pose a real threat to public safety; however, their effectiveness is largely determined by the clarity of the norms, the proportionality of the sanctions, and the consistency of enforcement. This study also found that provisions for compensation remain weak in many local regulations, even though victims of transmission may suffer medical, economic, and social losses that require clearer mechanisms for redress. In the post-COVID-19 context, local regulations need to be reformulated so that they not only emphasize punishment but also integrate prevention, compensation, and legal preparedness for future outbreaks.